Financial indépendance for local communities in the Algerian law - Boukhlefa, Badisali (Milev Journal of Research and Studies, 2023)
This study aims to evaluate the extent of financial indépendance for local communities in the Algerian law, it was conducted by relying on the legal texts that are related to local finance. The study concluded that the financial indépendance is weak for local communities and thatthey are relying mainly and increasingly on state subsidies. We have presented at the end some suggestions that help in strengthening the financial indépendance of local communities.